Combined mechanochemical and solid CO2 treatment for enhanced carbon uptake and performance of slag-based geopolymers - Sixiang Kang; Chenhao Song; Jize Wang; Wenda Wu; Tao Wang; Leiming Ling; Huaqiang Sun; Ying Lou; Xuefang Wang; Liwei Xu (Journal of CO2 Utilization)
In response to the high carbon emissions from cement production, carbon mineralization for CO2 sequestration and alternative cementitious materials have gained attention. However, carbon mineralization faces equipment and energy challenges, while geopolymer materials suffer from poor workability. This study proposes a novel method combining mechanochemical activation and dry ice (solid CO2) and explores its effects on the behavior of slag based geopolymer (SBG) mortar. This study demonstrates that, compared to the individual addition of dry ice or mechanical activation alone, using dry ice as a grinding medium allows it to embed into the particle structure in the form of distorted carbonates. The mechanochemical process continuously disrupts the carbonate layer, exposing fresh unreacted surfaces, thereby promoting ongoing reactions and significantly enhancing the carbon sequestration efficiency of SBG. While the addition of dry ice delays early hydration reactions, it promotes the generation of increasing hydration and carbonation products in the mid to late stages, enhancing the mortar's density and strength. Specifically, at a dry ice content of 2.7 % with mechanochemical processes, the comprehensive performance of SBG mortar is optimal after mechanochemical mixing, exhibiting moderate workability (214 mm fluidity), high compressive strength (54.8 MPa at 28d), low drying shrinkage (623µε at 28d), and strong resistance to chloride ion penetration (1884.18 C electrical flux).